Lift-Drag Characteristics and Vortex Interaction Mechanisms of Two-Dimensional Tandem Airfoils - Yuan, Dajun (Simen Owen Academic Proceedings Series, 2026)
The aerodynamic performance of tandem airfoils arranged in fore-aft configurations has become an important subject in low Reynolds number aerodynamics, owing to its relevance for unmanned aerial vehicles, formation flight, and energy-efficient aircraft. While prior studies have clarified the influence of spacing and positioning on lift and drag, most have focused on time-averaged coefficients or steady conditions, leaving the dynamic relationship between vortex evolution and instantaneous aerodynamic forces insufficiently understood. This study employs large-scale transient numerical simulations to analyze two-dimensional tandem airfoils, with visualization supported by FieldView 20 and quantitative analysis performed in Tecplot. Aerodynamic coefficients, including lift, pressure drag, and viscous drag, were extracted for both fore and aft airfoils, and systematically correlated with transient vortex structures across representative time instants. The results demonstrate that the fore airfoil maintains quasi-steady performance with minimal coefficient fluctuations, serving as a stable aerodynamic baseline. By contrast, the aft airfoil exhibits strong unsteady oscillations in lift and drag, directly governed by vortex growth, detachment, and reattachment, as confirmed by surface pressure distributions and flow field contours. These findings bridge the gap between force production and vortex dynamics in tandem configurations, advancing theoretical understanding of unsteady aerodynamics and offering practical insights for UAV formation design and bio-inspired flight strategies.